EVALUASI KESEJAHTERAAN HEWAN KURBAN SEBELUM PEMOTONGAN DI KOTA SERANG - Jajang Deni; Heirmayani Suherman; Meetha R Pardhedhe (Universitas Mathla’ul Anwar Banten, 2022)
Animal Welfare is all matters related to the physical and mental condition of Animal by Animal natural behavior that need to be applied and enforced to protect Animal from any person action who is not worthy to the Animal that are exploited by human (Act No. 41 of 2014 concerning husbandry and animal health). This study was conducted to evaluate the animal welfare of kurban animal during pre-slaughter in the city of Serang. This study is descriptive study conducted through observation and interviews with kurban commite 1438 H (2017 M) at thirty point site of slaughter. Some critical point of animal welfare assessment in this study are unloading, animal rest time before slaughter, availability water, animal crush, and knife sharpness for slaughtering animals. The result showed that 88,89 % implemented the principles of animal welfare.There are need to strengthen the implementation of animal welfare , the awareness of kurban committee about the importance of animal welfare, and the training of handlers participating in pre-slaughter.